Initiating pollen sensitization – complex source, complex mechanisms. Issue 1 (31st August 2020) - Pointner, Lisa; Bethanis, Athanasios; Thaler, Michael; Traidl‐Hoffmann, Claudia; Gilles, Stefanie; Ferreira, Fatima; Aglas, Lorenz
Abstract: The mechanisms involved in the induction of allergic sensitization by pollen are not fully understood. Within the last few decades, findings from epidemiological and experimental studies support the notion that allergic sensitization is not only dependent on the genetics of the host and environmental factors, but also on intrinsic features of the allergenic source itself. In this review, we summarize the current concepts and newest advances in research focusing on the initial mechanisms inducing pollen sensitization. Pollen allergens are embedded in a complex and heterogeneous matrix composed of a myriad of bioactive molecules that are co‐delivered during the allergic sensitization. Surprisingly, several purified allergens were shown to lack inherent sensitizing potential. Thus, growing evidence supports an essential role of pollen‐derived components co‐delivered with the allergens in the initiation of allergic sensitization. The pollen matrix, which is composed by intrinsic molecules ( e.g. proteins, metabolites, lipids, carbohydrates) and extrinsic compounds ( e.g. viruses, particles from air pollutants, pollen‐linked microbiome), provide a specific context for the allergen and has been proposed as a determinant of Th2 polarization. In addition, the involvement of various pattern recognition receptors (PRRs), secreted alarmins, innate immune cells, and the dependency of DCs in driving pollen‐induced Th2 inflammatory processes suggest that allergic sensitization to pollen most likely results from particular combinations of pollen‐specific signals rather than from a common determinant of allergenicity. The exact identification and characterization of such pollen‐derived Th2‐polarizing molecules should provide mechanistic insights into Th2 polarization and pave the way for novel preventive and therapeutic strategies against pollen allergies.